Distinct Immune Imprints of Post–Liver Transplantation Hepatitis C Persist Despite Viral Clearance. Issue 6 (8th June 2021) - Aregay, Amare; Engel, Bastian; Port, Kerstin; Vondran, Florian W.R.; Bremer, Birgit; Niehaus, Christian; Khera, Tanvi; Richter, Nicolas; Jaeckel, Elmar; Cornberg, Markus; Taubert, Richard; Wedemeyer, Heiner
Abstract : Recurrence or de novo infection of hepatitis C virus (HCV) after liver transplantation (LT) has been associated with progressive graft hepatitis that can be improved by treatment with novel direct‐acting antivirals. Cases of rejection episodes have been described during and after HCV treatment. The evolution of innate and adaptive immune response during and after cure of HCV LT is unknown. We studied 74 protein biomarkers in the plasma of LT patients receiving antiviral therapy. In addition, deep immune phenotyping of both the myeloid and lymphoid immune cell subsets in peripheral blood mononuclear cells was performed. We found that LT patients with active HCV infection displayed distinct alterations of inflammatory protein biomarkers, such as C‐X‐Cmotif chemokine 10 (CXCL10), caspase 8, C‐C motif chemokine 20 (CCL20), CCL19, interferon γ, CUB domain‐containing protein 1 (CDCP1), interleukin (IL)‐18R1, CXCL11, CCL3, IL8, IL12B, tumor necrosis factor‐beta, CXCL6, osteoprotegerin, IL10, fms‐related tyrosine kinase 3 ligand, hepatocyte growth factor, urokinase‐type plasminogen activator, neurotrophin‐3, CCL4, IL6, tumornecrosis factor receptor superfamily member 9, programmed death ligand 1, IL18, and monocyte chemotactic protein 1, and enrichment of peripheral immune cell subsets unlike patients without HCV infection who received transplants. Interestingly, patients who cleared HCV after LT did not normalize the altered inflammatory milieu nor did the peripheral immune cell subsets normalize to what would be seen in the absence of HCV recurrence. Overall, these data indicate that HCV‐specific imprints on inflammatory analytes and immune cell subsets after LT are not completely normalized by therapy‐induced HCV elimination. This is in line with the clinical observation that cure of HCV after LT did not trigger rejection episodes in many patients.